Factors related to adherence with the implementation of COVID-19 health protocols in a traditional market traders' community in East Java, Indonesia - Wahidah,; Widyawati, Ika Yuni; Dewi, Lingga Curnia; Khatijah Lim, Abdullah * (PMA House in Karachi, Pakistan, 2023)
Objectives: To observe the relationship of perceived seriousness, perceived susceptibility, perceived benefits, perceived barriers and cues to action with adherence to coronavirus disease-2019 protocols among traders.